Ecological information and education of Bălți university users (Confluenţe Bibliologice, 2026)
The article describes the scientiﬁc ﬁeld of the Environmental Decade programme: harnessing the Scientiﬁc Library collections in the greater interest of the students, pupils, teachers, related environmental issues; Informing/consulting in matters of environment and ecology through traditional and on-line exhibitions, through Scientiﬁc Library website page; TVclips Environmental Decade at the TV in the library lobby; Organization of scientiﬁc events (public lectures on issues of environmental protection, nutrition, health, bibliographic and thematic bibliographic reviews, thematic exhibition presentations in Power Point, national and international databases, presentations) that provides a framework for debate and speciﬁc initiatives, cooperation with faculties, high school and college, promotion in the Mass Media, Radio Moldova News.
Keywords: informative activities; cultural activities